Efficacy of selective nerve root block in lumbar radiculopathy in police force - Thakur, Gopesh Kumar; Dumre, Arjun Prasad; Lamichhane, Norman; Pokharel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Lumbosacral radicular pain due to disc herniation is one of the common disabling conditions in orthopaedic clinics. Most of these patients generally recover well even with non-operative treatment. Selective Nerve Root Block (SNRB) is one of the non-operative procedures for lumbar radiculopathies, both for diagnostic and therapeutic purpose. The aim of our study was to evaluate the efficacy of SNRB in lumbar radiculopathy patients of Nepal Police force due to single level disc prolapse.METHODS: This study was conducted at Nepal Police Hospital from January 2019 to June 2019. There were 29 radicular pain patients who were confirmed by MRI. All patients who met the inclusion criteria were subjected to SNRB with 80 mg of injectable methylprednisolone and 2 ml of 2 % lignocaine. Outcome of the treatment was prospectively evaluated till 6 months of follow up using Numeric Rating Scale (NRS) and Roland Morris Disability Questionnaire (RMDQ).RESULTS: Twenty (69%) patients had disc prolapse at L4-L5 level. Right sided radiculopathies were common (n=19, 65.5%) among them. There was improvement in Numeric Rating Scale (NRS) from pre-procedure average 8.37 to 2.8 post-procedure and Roland Morris Disability Questionnaire (RMDQ) from 15.18 to 6.8 at 6 months follow up. Two cases (6.9%) had to undergo discectomy after 6 weeks of SNRB due to relapse of symptoms.CONCLUSION: Selective Nerve Root Block is effective in immediate reduction of pain in patients with single level disc prolapsed with lumbar radiculopathy. It decreases the disability even in the high level of activity patients like Police personnel.